Seblak Edukasi: Savory Knowledge, Spicy Challenges. Interactive Media to Increase Learning Motivation of Junior High School Students - Wahyuni Sartini; Neni Wahyuningtyas (JURNAL PENDIDIKAN IPS, 2025)
Low learning motivation is one of the challenges in learning social studies, especially on the material of natural and social appearance. This research aims to develop interactive learning media “Seblak Edukasi” as an effort to increase the learning motivation of seventh grade students. This research uses the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The instruments used in this research are material expert validation sheets, media experts, and student response questionnaires. The validation results showed that Seblak Edukasi media was declared very feasible by material experts (92%) and media experts (92.3%), and received very positive responses from students (95.6%). This media combines elements of traditional games, visual approach, and utilization of digital technology (QR code), so as to create an interesting, active, and fun learning atmosphere. More than just a medium, Seblak Edukasi is a form of leadership for prospective teachers in designing adaptive, creative, and contextual 21st century learning, as well as a real contribution in supporting the transformation of education towards the Golden Indonesia 2045.